Interactive Website Media to Improve Learning Outcomes of Chemical Bonding Materials - Nurjihan Aulia Fitri; Achmad Lutfi (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This research aims to obtain website which is feasible to improve student learning outcomes in chemical bonding material. This research uses Research and Development (R&D) with a 4-D model but limited to stages develop. Qualifications website developed is guided by validity, practicality and effectiveness. Data was obtained by filling out a validation questionnaire to determine validity website; response questionnaires and student activity observation sheets to find out practicality website; as well as learning outcomes tests to determine effectiveness website. The research results show that website that was developed can be declared valid by obtaining a modus score of 5. Website there was an increase in learning outcomes which were analyzed using the classical completeness test and the Wilcoxon test. The percentage results of the classical completeness test were 96.87% of students who were declared complete and the Wilcoxon test results obtained a sig value. of 0.000. From the results of this analysis website developed can be said to be effective. Based on the results of the validity and effectiveness analysis, it was found that website developed is suitable for use as learning media.